The interaction of miR-181a-5p and sirtuin 1 regulated human bone marrow mesenchymal stem cells differentiation and apoptosis. Issue 1 (1st January 2021) - Zhu, Haitao; Chen, Hua; Ding, DeGang; Wang, Shui; Dai, XiaoFeng; Zhu, YuLong
ABSTRACT: Osteoporosis (OP) characterizes a decrease in bone density and bone mass which leads to brittle fractures and serious damages to individuals. In recent years, various researches have proved that miRNAs act pivotally in the onset of bone-related diseases. In our research, we probed into the impact of miR-181a-5P on viability, differentiation, as well as apoptosis of human bone marrow mesenchymal stem cells (hBMSCs). Our study reported that overexpressing miR-181a-5p considerably reduced the cell growth, whereas the miR-181a-5p inhibition showed opposite results. Furthermore, the hBMSCs apoptosis percentage was visually elevated or minimized after overexpressing or silencing miR-181a-5p, respectively. Our data also indicated that miR-181a-5p overexpression significantly inhibited ALP activity, and level of OPN, Runx2 and OCN at mRNA and protein level, whereas miR-181a-5p inhibition presented opposite results. In addition, based on luciferase reporter assay, sirtuin 1 (Sirt1) was confirmed as the target of miR-181a-5p in hBMSCs. Finally, Sirt1 overexpression significantly inhibited the impact of miR-181a-5p mimic on apoptosis and inhibited differentiation, while silencing Sirt1 eliminated the inhibitory effects of miR-181a-5p on apoptosis and promoted differentiation via PI3K/AKT pathway. In conclusion, this work revealed that miR-181a-5p could regulate hBMSCs apoptosis as well as differentiation via regulating Sirt1/PI3K/AKT signaling pathway. Graphi Cal Abstract